Mammoth orbitofrontal neurofibromatosis with herniating meningo-encephalocele - Dhanraj Prema; Paul Kingsly; Lamba Shashank; Shetty Rahul (Indian Journal of Plastic Surgery)
We are presenting a mammoth orbito-frontal neurofibroma with a herniating meningo-encephalocele in a 23 year old African male. The tumour measured 87cm Χ 54cm and occupied the right orbito-temporo-facial region and had destroyed the right orbit. A pre operative embolization of the feeding vessels was followed by a one stage near total excision of the tumour and repair of the meningo-encephalocele in hypotensive anaesthesia. The excised tumour weighed 8 Kg and, to the best of our knowledge, is the largest orbito-facial neurofibroma reported in literature.